NOTARY/LAND DEED OFFICIALS RESPONSIBILITY FOR THE DRAFTING OF A HOUSE SALE AND PURCHASE DEED USING A FAKE DIVORCE DEED BY THE APPEARERS - SHARINA AGGRABANU (Law Research Review Quarterly, 2026)
This article examines the legal responsibility of a notary who concurrently acts as a Land Deed Official in the making of a house sale and purchase deed based on a forged divorce certificate submitted by an appearer. The main issue arises when the forged document is used to avoid spousal consent over joint marital property, while the identity card records the seller as divorced. The research applies normative juridical method supported by statutory, conceptual, and case-based approaches. The analysis shows that the authenticity of a deed must be separated from the validity of the underlying legal act. A deed made by an authorized official may retain formal authenticity, yet the sale and purchase may be annulled when the seller lacks authority to dispose of joint property. The notary/Land Deed Officials is not a guarantor of all material truth, but the office requires reasonable verification of identity, marital status, court authority, land documents, and visible irregularities. Civil liability arises when negligence, loss, and causality are proven. Criminal liability requires knowledge, intent, or participation in the use of forged documents. Administrative and ethical sanctions may follow when professional prudence is ignored. This article proposes an integrated verification standard involving courts, civil registration offices, and land offices to protect parties and officials who act in good faith.